2020
DOI: 10.13057/biodiv/d211201
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of plants and arthropods in soybean agro-ecosystems in the Grassland Biome of South Africa

Abstract: Abstract. Janse van Rensburg PD, Siebert SJ, Masehela T, Ellis S, Van den Berg J. 2020. Diversity patterns of plants and arthropods in soybean agroecosystems in the grassland biome of South Africa. Biodiversitas 21: 5559-5570. Soybean is widely cultivated in the grassland biome of South Africa (ca.  800 000 ha per annum). Yet the possible effects that large-scale cultivation of soybean has on biodiversity in adjacent habitat are not fully understood. This study aimed to describe the plant and arthropod species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
2
4
1
Order By: Relevance
“…This could be attributed to herbicide application in the fields which suppresses dominant weeds. This contrasted the findings of Janse van Rensburg et al (2020), who found soybean crop fields to have significantly lower evenness than the boundary. In that instance, the factors that reduced evenness were chemical application and grazing disturbance.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This could be attributed to herbicide application in the fields which suppresses dominant weeds. This contrasted the findings of Janse van Rensburg et al (2020), who found soybean crop fields to have significantly lower evenness than the boundary. In that instance, the factors that reduced evenness were chemical application and grazing disturbance.…”
Section: Discussioncontrasting
confidence: 97%
“…Agricultural disturbance affects plant diversity in field margins due to grazing but also herbicide drift (Khan et al 2017). The observed lower diversity in margins was also found in other studies, for example, Janse van Rensburg et al (2020) reported lower plant diversity in the field margins adjacent to crop fields that were treated with herbicides. Schmitz et al (2014) observed the same effect due to fertiliser drift from fields into the margin.…”
Section: Discussionsupporting
confidence: 78%
“…We recorded C. millari for the first time during surveys of arthropod diversity associated with Encephalartos species in AENP in July 2022 ( Janse van Rensburg et al 2022 ). During these initial surveys, we visited approximately 200 E. longifolius , 50 E. lehmannii , and 50 E. caffer plants ( Janse van Rensburg et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…We recorded C. millari for the first time during surveys of arthropod diversity associated with Encephalartos species in AENP in July 2022 ( Janse van Rensburg et al 2022 ). During these initial surveys, we visited approximately 200 E. longifolius , 50 E. lehmannii , and 50 E. caffer plants ( Janse van Rensburg et al 2022 ). Callioratis millari was not found on E. longifolius or E. lehmannii , although the presence of Z. lepida on these plants was confirmed ( Janse van Rensburg et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Complex interactions between abiotic and biotic components in ecosystems determine the quantity, quality and reliability of these services (Mace et al 2012). In grassy landscapes, the herbaceous layer provides forage and habitat to arthropods (Botha et al 2017, Janse Van Rensburg et al 2020). These herbaceous layers can be very diverse and thus provide more habitat and foraging opportunities, especially for predacious arthropods.…”
Section: Introductionmentioning
confidence: 99%